ỨNG DỤNG MÔ HÌNH SWAP VÀ IQQM TRONG QUẢN LÝ TỔNG HỢP LƯU VỰC SÔNG BA - Cư, Nguyễn Văn; Sơn, Nguyễn Thái (Vietnam Journal of Earth Sciences, 2017)
lntergrated catchment management is aregional and international issue with natural concern, especially in Vietnam, for socio -economic development and stable enviroment protection. Along with the comprehensive information technology development, modelizationis the strong and necessary in river basin researching and management. The authors have applied 2 models: SWAP and lOOM in searchingand general managing the Ba river basin because of their strong caculation ability and useful functions. Base on the input information of OEM,weather, vegetation cover and landuse, the resultsof application of SWAP and IQQM modes in Ba river allowed to estimate the quality and imitation of water according to many different solutions.